PP29 Aftermath of COVID-19 pandemic on mental health and wellbeing of patients with thalassemia major in Pakistan: a qualitative study. Issue 9 (23rd August 2022) - Hammad, Muhammad
Abstract : Background: Chronic patients with thalassemia major were mainly recognized as more prone to bad mental health during COVID-19 pandemic. However, why this populace has confronted these detrimental effects, how they have skilled them and the way they have coped, stays under-explored. Aim: The aim was to evaluate the aftermath of COVID-19 pandemic on mental health and wellbeing of patients with thalassemia major and to identify the coping strategies to overcome the effects. Methods: The present qualitative study was conducted through in-depth face-to-face semi-structured interviews held with 21 patients with thalassemia major selected through probability consecutive sampling. All interviews were recorded, transcribed, and analysed with reflexive thematic analysis. Results: The most commonly described mental health condition was depression and concern of overall health status. Seven associated pandemic elements contributed in deterioration of mental health: i) Isolation at home, ii) Disrupt transfusion services, iii) Change in appetite and interests, iv) Uncertainty and lack of control, v) Intensive media coverage, vi) Worsening of chronic health problems, vii) Difficulty in sleeping. Four coping strategies were identified for maintaining mental health: i) Practicing gratitude ii) Engaging in hobbies and activities, iii) Stay connected with others, iv) Discern social support. Conclusions: Thalassemia major patients had been negatively affected during the pandemic. However, it seems a temporary respite for few, drew upon reserves of resilience and tailored their coping techniques to hold high quality wellbeing.